The Influence of Hedonic Motivation and Influencer Marketing on Purchasing Decisions with FOMO (Fear of Missing Out) as A Mediating Variable (Empirical Study: Cupika Online Store Customers) - Stephanus Solaiman; Christian Haposan Pangaribuan (PT Inovasi Pratama Internasional, 2024)
This study investigates the influence of hedonic motivation and influencer marketing on purchase decisions, with Fear of Missing Out (FOMO) as a mediating variable, in the context of Cupika online store customers. The research employs a quantitative approach using structural equation modeling (SEM) with a sample of 132 respondents who have purchased from Cupika's e-commerce platforms. The findings reveal significant direct effects of hedonic motivation (β = 0.206, p = 0.017) and influencer marketing (β = 0.317, p < 0.001) on purchase decisions. FOMO demonstrates a strong direct effect on purchase decisions (β = 0.470, p < 0.001). Furthermore, the study identifies significant indirect effects of hedonic motivation (β = 0.243, p = 0.001) and influencer marketing (β = 0.149, p = 0.006) on purchase decisions, mediated by FOMO. These results highlight the complex interplay between emotional factors, social influence, and psychological states in shaping online consumer behavior. The study contributes to the growing body of literature on digital consumer behavior and offers practical implications for e-commerce marketing strategies. It underscores the importance of leveraging hedonic appeals, influencer partnerships, and FOMO-inducing tactics to drive online sales. However, it also emphasizes the need for ethical considerations in implementing such strategies. Future research directions include exploring these relationships across various product categories and cultural contexts, and investigating the long-term impacts of FOMO-driven purchases on consumer satisfaction and brand loyalty.